2012
DOI: 10.1088/1367-2630/14/5/053008
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinary epitaxial alignment of graphene islands on Au(111)

Abstract: Pristine, single-crystalline graphene displays a unique collection of remarkable electronic properties that arise from its two-dimensional, honeycomb structure. Using in situ low-energy electron microscopy, we show that when deposited on the (111) surface of Au carbon forms such a structure. The resulting monolayer, epitaxial film is formed by the coalescence of dendritic graphene islands that nucleate at a high density. Over 95% of these islands can be identically aligned with respect to each other and to the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
79
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(93 citation statements)
references
References 44 publications
13
79
0
1
Order By: Relevance
“…In this paper, we will give an overview on recent experimental and theoretical investigations to understand the growth morphology and thermal stability of metal nanostructures and thin film grown on grapheme [71][72][73][74][75][76][77][78]. We note diverse efforts have been made to synthesize graphene with different approaches, such as exfoliation and cleavage from graphite [1], chemical vapor deposition on metal surfaces [79][80][81][82][83][84][85][86][87][88], carbon deposition on single crystal metal surfaces under ultra high vacuum (UHV) conditions [83,89] and thermal annealing of SiC [90][91][92][93][94][95]. It is not the scope of this paper to review the growth and preparation of graphene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we will give an overview on recent experimental and theoretical investigations to understand the growth morphology and thermal stability of metal nanostructures and thin film grown on grapheme [71][72][73][74][75][76][77][78]. We note diverse efforts have been made to synthesize graphene with different approaches, such as exfoliation and cleavage from graphite [1], chemical vapor deposition on metal surfaces [79][80][81][82][83][84][85][86][87][88], carbon deposition on single crystal metal surfaces under ultra high vacuum (UHV) conditions [83,89] and thermal annealing of SiC [90][91][92][93][94][95]. It is not the scope of this paper to review the growth and preparation of graphene.…”
Section: Introductionmentioning
confidence: 99%
“…We also note that in the literature, growth of various metals on graphene with different substrate (e.g., on Si-terminated SiC, SiO 2 , or on transition metal surfaces) have been reported, but with the growth outcome depending on the type of graphene and the substrate is grown on. For example, for graphene grown on metals, the moiré pattern formed between graphene and the metal substrate on Cu(111) [86], Ni (111) [85,87], Au (111) [88], Ru(0001) [22,25,30], and Ir (111) [27][28][29][79][80][81] have been considered as a good substrate for patterned growth of metal clusters networks. The reason for this is because the graphene substrate interaction is strong so the moiré supercell provides the nucleation sites for the deposited atoms to aggregate regular island distributions.…”
Section: Introductionmentioning
confidence: 99%
“…Strong interaction also results in formation of a single graphene domain. Weak interaction with graphene is observed on Cu [18], Ir [19], Pt [20], and Au [21] substrates, and there the π-band dispersion of free standing graphene is preserved around the K point and no gap appears at the Dirac point. However, rotational disorder is commonly observed for graphene grown on weak interacting metals, i.e.…”
Section: Cvd Growth Of Graphene On Metalsmentioning
confidence: 99%
“…Toward this goal, we have carried out in-situ observations of graphene growth by carbon deposition in LEEM using a solid graphite and an isotopically enriched 13 C graphite sources. The isotope labeling also provides us a fundamental understanding of the graphene-substrate interface structure using Raman spectroscopy ( Figure 5).…”
Section: Carbon Deposition For Growing Graphene On Silicon Carbidementioning
confidence: 99%
“…We overcame this challenge by growing graphene on Au(111) by depositing evaporated C, which is a manufacturable process. We found that we could synthesize graphene in which about 95% of the domains were closely aligned to a single in-plane orientation ( Figure 12) [13]. Complete films were achieved through the C deposition approach.…”
Section: Au Is An Excellent Substratementioning
confidence: 99%